1988
DOI: 10.2737/psw-gtr-104
|View full text |Cite
|
Sign up to set email alerts
|

The San Dimas experimental forest: 50 years of research

Abstract: USDA Forest Service Gen. Tech. Rep. PSW-104. 1988 'Unless otherwise noted, available and unpublisheddata areon file in the SDEF archives at the Forest Fire Laboratory,4955 CanyonCrest Drive, Riverside, California 92507.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
42
0
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 55 publications
0
42
0
1
Order By: Relevance
“…The lysimeter installation is located within the San Dimas Experimental Forest, a U.S. Forest (Dunn et al, 1988). The lysimeters consist of large (5.3 by 5.3 m horizontally and 2.1 m deep) earthen-walled pits that were ®lled in 1937 with ®ne sandy loam (58% sand, 31% silt, 11% clay) derived on site from the weathering of diorite (Colman and Hamilton, 1947).…”
Section: Site Descriptionmentioning
confidence: 99%
“…The lysimeter installation is located within the San Dimas Experimental Forest, a U.S. Forest (Dunn et al, 1988). The lysimeters consist of large (5.3 by 5.3 m horizontally and 2.1 m deep) earthen-walled pits that were ®lled in 1937 with ®ne sandy loam (58% sand, 31% silt, 11% clay) derived on site from the weathering of diorite (Colman and Hamilton, 1947).…”
Section: Site Descriptionmentioning
confidence: 99%
“…Krammes (1969) reported that the soil and bedrock are similar hydrologically, with |70% of the porosity being noncapillary. The Mediterranean climate provides cool, wet winters and hot, dry summers with an annual temperature range of about 24 to 388C (Dunn et al, 1988). Most precipitation occurs as rain.…”
Section: Environmental Settingmentioning
confidence: 99%
“…Most precipitation occurs as rain. Historically, annual precipitation varied from 258 to 1595 mm, with a mean of 678 mm (Dunn et al, 1988). Native vegetation is chaparral.…”
Section: Environmental Settingmentioning
confidence: 99%
See 1 more Smart Citation
“…The region is typi¢ed by a warm Mediterraneantype climate (mean annual temperature 14.4 8C) and, on average receives 678 mm precipitation per annum (Dunn et al 1988). The soils within the basin are composed of sandy loams or sandy clay loams that are derived from a weathered granite or granodiorite (United States Department of Agriculture 1971), tend to be slightly acidic (pH 5.8^6.0) and contain signi¢cant reserves of phosphorous (mean 30 mg g 71 , HCO 3 -extractable) and potassium (200 mg g 71 ).…”
Section: (A) Site Description and Sampling Proceduresmentioning
confidence: 99%